A systematic comparison of the developmental vascular toxicity of bisphenol A and its alternatives in vivo and in vitro. (March 2022) - Ji, Guixiang; Gu, Jie; Guo, Min; Zhou, Linjun; Wang, Zhen; Shi, Lili; Gu, Aihua
Abstract: Due to the potential toxicity of bisphenol A (BPA), several bisphenols (BPs), including bisphenol F (BPF), bisphenol S (BPS) and bisphenol AF (BPAF), have been gradually used as its main substitutes, and the levels of these alternatives in different environmental media have been constantly increasing. Although some previous studies have shown that bisphenol substitutes have similar or greater acute toxicity and estrogenic effects than BPA, comparative studies on the cardiovascular toxicity of BPs have not been evaluated. In this study, the developmental vascular toxicity of BPA and three predominant substitutes (BPF, BPS and BPAF) were evaluated using zebrafish embryos and human vascular endothelial cells (HUVECs). BP exposure at a sublethal concentration of 1/10 96 h median lethal concentration (96 h-LC50 ) significantly hindered intersegmental vessel (ISV) growth, delayed common cardinal vein (CCV) remodeling and decreased subintestinal vessels (SIVs) in Tg ( fli1 :EGFP) zebrafish embryos. Meanwhile, the results of the endothelial tube formation assay showed that in vitro angiogenesis was inhibited by BP exposure. Mechanistically, BP exposure increased oxidative stress characterized by a significant decrease in superoxide dismutase (SOD) and catalase (CAT) activity, accompanied by increased levels of malondialdehyde (MDA) and reactive oxygen species (ROS) in both zebrafish and HUVECs. Therefore, the vascular toxicity and oxidative stress potency of the BPs were compared and evaluated, ranking as follows: BPAF > BPF > BPA > BPS. To the best of our knowledge, the present work, for the first time, systematically provides direct evidence for BPA and its alternatives on developmental vascular toxicity in vitro and in vivo . Therefore, these findings will provide insight into the rational and safe application of BPA substitutes. Graphical abstract: Image 1 Highlights: BPs induced vascular toxicity in zebrafish in vivo. BPs exposure significantly inhibited angiogenesis in vitro. BPs exposure dramatically increased the oxidative stress. The vascular toxicity of BPs: BPAF > BPF > BPA > BPs.